2022
DOI: 10.3390/ma15072374
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Doped Upconversion Luminescent Nanoparticles—Evolving Role in Bioimaging, Biosensing, and Drug Delivery

Abstract: Upconverting luminescent nanoparticles (UCNPs) are “new generation fluorophores” with an evolving landscape of applications in diverse industries, especially life sciences and healthcare. The anti-Stokes emission accompanied by long luminescence lifetimes, multiple absorptions, emission bands, and good photostability, enables background-free and multiplexed detection in deep tissues for enhanced imaging contrast. Their properties such as high color purity, high resistance to photobleaching, less photodamage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 131 publications
0
7
0
1
Order By: Relevance
“…Therefore, the study demonstrated the application of photosensitized TbNPs bioconjugates for biosensing and bioimaging. These prepared nano bioconjugates also showed binding to that of the transmembrane epidermal growth factor receptors; thus, the prepared formulation can be utilized as stable luminescence markers for intercellular signaling. ,, …”
Section: Terbium-based Nps (Tbnps) For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the study demonstrated the application of photosensitized TbNPs bioconjugates for biosensing and bioimaging. These prepared nano bioconjugates also showed binding to that of the transmembrane epidermal growth factor receptors; thus, the prepared formulation can be utilized as stable luminescence markers for intercellular signaling. ,, …”
Section: Terbium-based Nps (Tbnps) For Biomedical Applicationsmentioning
confidence: 99%
“…These prepared nano bioconjugates also showed binding to that of the transmembrane epidermal growth factor receptors; thus, the prepared formulation can be utilized as stable luminescence markers for intercellular signaling. 44,122,123 The Tb (III)-guanosine monophosphate-mercury(II) coordination polymeric NPs have been utilized previously to FRET pair with the help of the nanoprism for the development of the biosensor. The work employed a modified lanthanidebinding peptide containing tryptophan that efficiently sensitizes bound lanthanide ions, resulting in the creation of a trypsin cleavage site.…”
Section: Terbium-based Nps (Tbnps) For Biomedical Applicationsmentioning
confidence: 99%
“…Considering the complexity of many UCNP systems, the long-term stability and biosafety of these nanoparticles need to be seriously investigated. More research is also needed into the effects of UCNPs on the nervous and immune systems in humans ( Jethva et al, 2022 ).…”
Section: Limitations For Upconversion Nanoparticle-based Antibacteria...mentioning
confidence: 99%
“…Rapid advances in nanotechnology have brought promising revolution and cutting-edge research in biomedicines exclusively in cancer therapy, bioimaging, and regenerative medicine [1,2]. In this respect, various types of nanomaterials are being developed for biomedical applications such as the delivery of therapeutic agents (drugs, peptides, genes, mRNA), bio-imaging and tissue engineering, etc [3][4][5][6][7][8]. Numerous nanomaterials are also introduced as nanotherapeutics which not only serve as anticancer agents but are also used as efficient nanocarriers for targeted drug delivery for minimization of drug distribution in healthy tissues [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%